On SAS-Injective Rings - Chyad, Heba Hadi; Mehdi, Akeel Ramadan (Iraqi Journal of Science, 2024)
Let  be a ring. A right -module  is called SAS- -injective (where  is any right -module) if every right -homomorphism from a semiartinian small right submodule of  into  extends to . A ring  is called right SAS-injective if  is SAS- -injective module. Right SAS-injective rings are studied in this paper. Many characterizations and properties of this type of  rings are obtained.